2005
DOI: 10.3171/jns.2005.102.s_supplement.0128
|View full text |Cite
|
Sign up to set email alerts
|

Gamma knife surgery for brain metastases from lung cancer

Abstract: The risk-benefit ratio of GKS in this series was satisfactory. There was no difference in response rates of the two tumor types, and WBRT did not improve the duration of survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 24 publications
7
53
1
3
Order By: Relevance
“…8,33 Recent publications have indicated that WBRT has no survival benefit, no improvement in functional independence, and a negative impact on quality of life. 5,16,26,32 In our study, the survival from the time of SRS was shorter by longer than 2 months in the WBRT-treated group. However, the statistical significance was neutralized when the survival from diagnosis of brain metastasis was analyzed.…”
Section: Discussion Survivalmentioning
confidence: 71%
“…8,33 Recent publications have indicated that WBRT has no survival benefit, no improvement in functional independence, and a negative impact on quality of life. 5,16,26,32 In our study, the survival from the time of SRS was shorter by longer than 2 months in the WBRT-treated group. However, the statistical significance was neutralized when the survival from diagnosis of brain metastasis was analyzed.…”
Section: Discussion Survivalmentioning
confidence: 71%
“…Radiosurgery is not always applicable for large cystic brain metastases. Pan et al (17) reported that GKRS alone could not control the large cystic components (>10 ml) effectively. When applied to the solid component of the tumor, the combination of stereotactic cyst aspiration and GKRS resulted in a good outcome, with a 1-year survival rate of 60%.…”
Section: Discussionmentioning
confidence: 99%
“…Positive influence of controlled primary site has been reported in multivariate study (Sneed, 2002) and in univariate studies (Lorenzoni, 2004;Jawahar, 2004;Pan, 2005;Kased, 2009). Some studies did not find significant influence (Chidel, 2000;Hernández, 2002;Golden, 2008).…”
Section: Control Of the Primary Tumormentioning
confidence: 98%
“…After a Gamma Knife treatment for brain metastases, along the time new metastases can develop, in such situations a new Gamma Knife treatment can be offered to these patients, Pan (Pan, 2005) found a positive influence on survival the realization of a new treatments in multivariate analysis. Vesagas (Vesagas, 2002) and Yu (Yu, 2005) found benefice in univariate studies.…”
Section: Multiple Lgk Treatmentsmentioning
confidence: 99%